Exploring the potential of an oyster (Saccostrea mordax) in oligotrophic seas: Effects of starvation on physiological and molecular regulation - Shuming Guo; Liqiang Zhao; Yuexin Zhao; Zohaib Noor; Xiaogang Yang; Shiwei Fu; Zhen Zhao; Weitao Wan; Jinkuan Wei; Yanping Qin; Haitao Ma; Ziniu Yu; et al. (Aquaculture Reports)
Starvation is the most common physiological challenge for marine bivalves, especially in oligotrophic seas like the South China Sea. Its dominant oyster species, Saccostrea mordax, remains unclear regarding starvation tolerance and underlying mechanisms. Here, we treated S. mordax with starvation for four months. Compared with the control group, no significant decrease in survival was observed in starvation-treated S. mordax. A significant decrease in oyster respiration rate was observed from the 14th day, and on the 90th day, the activities of Superoxide dismutase (SOD) and Catalase (CAT), and the content of Malondialdehyde (MDA) in the gill of oyster decreased. Besides, we found that oysters had a slow process of morphological deterioration in different tissues (gill, digestive gland, muscle) under starvation treatment. The integration of transcriptomics analyses indicates that the metabolic capacity of oysters decreases under prolonged starvation, and the expression of genes in the solute carrier family that contribute to nutrient transport was down-regulated. Moreover, the down-regulation of the expression of immune-related genes, such as the IAP gene family, MYD88, and CDC42, indicated that the homeostasis between apoptosis and cell proliferation was disrupted, which was in agreement with the results of sections with the enlarged lumen of the digestive gland and apoptosis of digestive cells. On the contrary, most genes in the collagen family, that contribute to the stability of tissue structure, were up-regulated, which may contribute to long-term tolerance to starvation. Overall, our study reveals the physiological responses and mechanisms of starvation tolerance in S. mordax, which has the potential to contribute to the restoration of island reefs in oligotrophic seas.